Job stress among humanitarian aid workers - Jachens, Liza.J. (2018)
Objective: This thesis examined the prevalence of burnout, alcohol consumption, and psychological distress and their association with stress-related working conditions – defined either in terms of the Effort-Reward Imbalance (ERI) model, or the ERI model combined with the Job Demand-Control-Support (job strain) model (DCS) – in two large-scale international samples of humanitarian aid workers. The studies herein were the first in the extant literature to examine organisational stressors using job stress models in this occupational group. Furthermore, given the paucity of previous research on the subjective stress-related experiences of humanitarian aid workers, this thesis also contains an interview-based study that explored how humanitarian aid workers perceived the transactional stress process. One key characteristic of this thesis was that both quantitative and qualitative approaches were utilised to provide a deep and ecologically valid understanding of the stressor-strain relationship. Identifying the links between stressful aspects of work and both psychological and behavioural health outcomes may help inform the design of sector-specific health interventions.